PENGARUH PROFIL RISIKO DAN MODAL INTELEKTUAL PADA RETURN ON ASSETS PERBANKAN - Negari, Sekarini Tirtha; Suartana, I Wayan; Tenaya, Agus Indra (E-Jurnal Akuntansi, 2017)
Bank profitability as measured by Return On Assets not only be seen from the value of tangible assets are derived from the measurement of financial ratios in the risk profile. If banking performance want to report more relevant, profitability was also measured of intangible assets derived from intellectual capital. This study aims to examine the influence of risk profile and intellectual capital with Return On Assets. The study use banking sector that listed on the Indonesia Stock Exchange in 2012-2015. Samples were obtained by 112 with purposive sampling. Techniques of data analysis is multiple linear. F statistical test results showed ratio of NPL, NIM, LDR, VAIC TM , CEE, HCE, and SCE ha s simultaneously affect on ROA. Statistical t test showed that NPL has negative effect on ROA. Ratio of NIM, VAICTM, HCE and SCE has positive effect on ROA. But for LDR and CEE has no effect on ROA.
Keywords: risk profile, intellectual capital, Return On Assets